KAJIAN PENERIMA FIDUSIA DENGAN JAMINAN GIRO YANG TIDAK DIDAFTARKAN OLEH DEBITUR YANG WANPRESTASI - APRILIA APRILIA (PREMISE LAW JURNAL, 2015)
Demand deposit is a banking term for the method of payment which is mostly reversed to checking system; it is an order to transfer a sum of money from one account to another as specified in the order. After a check is given to the payee who saves it in his bank account, while demand deposit is given by a payer to a payee’s bank and will transfer it to the payee’s bank account. The difference lies on the ‘push and pull’ system. A check is a ‘pull’ transaction; by showing a check, the bank that receives the payment will find its fund in the payer’s bank and will draw the money if it is available. If it is unavailable, the check will be ‘bounced’ and will be returned by informing that the fund is insufficient. On the other hand, a demand deposit is a ‘push’ transaction; a payer orders his bank to transfer his money in his account to the payee’s account so that the latter can withdraw it. Therefore, a demand deposit cannot be bounced since the bank only processes the order from the payer if there is enough fund in his account. Keywords: Giving Credit, Security, Legal Protection